Probing the Origin of Viscosity of Liquid Electrolytes for Lithium Batteries - Yao, Nao; Yu, Legeng; Fu, Zhong‐Heng; Shen, Xin; Hou, Ting‐Zheng; Liu, Xinyan; Gao, Yu‐Chen; Zhang, Rui; Zhao, Chen‐Zi; Chen, Xiang; Zhang, Qiang (Angewandte Chemie International Edition, 2023)
Viscosity is an extremely important property for ion transport and wettability of electrolytes. Easy access to viscosity values and a deep understanding of this property remain challenging yet critical to evaluating the electrolyte performance and tailoring electrolyte recipes with targeted properties. We proposed a screened overlapping method to efficiently compute the viscosity of lithium battery electrolytes by molecular dynamics simulations. The origin of electrolyte viscosity was further comprehensively probed. The viscosity of solvents exhibits a positive correlation with the binding energy between molecules, indicating viscosity is directly correlated to intermolecular interactions. Salts in electrolytes enlarge the viscosity significantly with increasing concentrations while diluents serve as the viscosity reducer, which is attributed to the varied binding strength from cation–anion and cation–solvent associations. This work develops an accurate and efficient method for computing the electrolyte viscosity and affords deep insight into viscosity at the molecular level, which exhibits the huge potential to accelerate advanced electrolyte design for next‐generation rechargeable batteries.